20 megahertz operation of organic nanodiodes. Issue 8 (19th February 2016) - Majewski, L. A.; Song, A. M.
Abstract : Solution‐processed polymer nanodiodes operating at frequencies up to 20 MHz are demonstrated. As the active layer, p‐type semiconductor poly(didodecylquarterthiophene) (PQT12) was used. It is shown that devices based on linear arrays of semiconducting polymer nanowires with intentionally broken symmetry display nonlinear current–voltage characteristics similar to conventional diodes. The so‐called self‐switching devices (SSDs) are single layered, planar structures that can be easily fabricated in a single step of nanolithography. The SSDs possess substantially lower parasitic capacitance between contacts than conventional organic diodes and organic thin‐film transistors, and we show that the nano‐rectifiers can operate at frequencies well above both 125/134 kHz and 13.56 MHz RFID communication bands.